Association Between Phase Angle and Sarcopenia in Patients Undergoing Peritoneal Dialysis - Do, Jun Young; Kim, A. Young; Kang, Seok Hui (Frontiers in Nutrition, 2021)
Introduction: There is limited data on the association between phase angle (PhA) and sarcopenia using both muscle strength and muscle mass in patients undergoing peritoneal dialysis (PD). We aimed to evaluate the association between PhA and sarcopenia in patients undergoing PD. Methods: We enrolled prevalent patients undergoing PD (n = 200). The patients were divided into tertiles based on their PhA level: low (n = 66; 1.9–4°), middle (n = 68; 4.1–4.9°), and high tertiles (n = 66; 5–8°). PhA was measured by a bioimpedance analysis. Handgrip strength (HGS) was measured in all the patients. Body compositions were measured by dual energy x-ray absorptiometry (DXA). Results: Handgrip strength (HGS) and/or lean mass indices showed poorer trends in the low tertile than in the other tertiles. PhA was positively associated with HGS and/or muscle mass index. Multivariate analyses showed that the patients in the low tertile had an odds ratio of 9.8 (p = 0.001) and 52.79 (p < 0.001) for developing sarcopenia compared with those in the middle and high tertiles, respectively. Subgroup analyses using these variables yielded results similar to those from the total cohort. Conclusion: This study demonstrated that PhA is independently associated with muscle mass, strength, and sarcopenia in patients undergoing PD. This result suggests that PhA can be used as a valuable and simple predictor for identifying patients undergoing PD who are at risk of sarcopenia.